Language Attitude of Youths in Malaysia Towards Korean Language - Jamari, Suzilla; Abdul Rahim, Zurahani (Development in Language Studies, 2023)
Culture and language are closely interrelated. Exposure to one would increase awareness of the other. While the Korean Wave has succeeded to enter Malaysian industries, the culture has also introduced Malaysian youths to the Korean language. This research aims to analyse the language attitudes of youths in Malaysia towards the Korean language. A new questionnaire was developed expressly for this study, focused on the participants’ affective attitudes towards the language. This study included 86 participants, and the findings suggested that adolescents in Malaysian have a favourable attitude about the language. The participants’ backgrounds are also found to be contributing to their positive attitude.